Ruanda: a produção de um genocídio - Fonseca, Danilo Ferreira da (2010)
The present research covers for the Rwandan historical process of century XX, more necessarily, from the beginning of the Belgian settling in 1917 until the end of the genocide in 1994, pointing the different moments and underlying factors that had led the event of the genocide s actions in the decade of 1990. For such, it was valued in the construction of the research the Rwanda s social practice, as much its traditions, as well as its relation with the capitalism s world. The intention is objectify the history of Rwanda beyond a process dichotomized in a mere ethnic relation between tutsis and hutus. Understanding the functioning of the particular Rwandan social metabolism, had also been displayed the formations and relations of social class in the middle of Rwandan history, and from these, and its particularitities, its contradictions and tensions that had led in 1994 the death of hundreds of thousand of Rwandans, calls generically of tutsis and moderate hutus. Thus, the Rwandan genocide also is presented beyond a conflict between two ethnics groups, but yes, decurrently of a particular historical process that bring local agents with global interlocutions